Facilitators’ Perceptions on Online Assessment in Public Higher Learning Institutions in Tanzania; A Case Study of the Institute of Accountancy Arusha (IAA) (International Journal of Scientific Research and Management (IJSRM), 2022)
Reliance on computerised systems for both learning and conducting research in learning environments has been proven to be of great importance in saving time and money to the institutions, teachers and students as well as the government in general. However, research on teachers’ perceptions of computer-assisted assessment is lacking. The study’s goal was to look into teachers’ perspectives on the use of computer-assisted assessments in Tanzanian public higher learning institutions, using the Institute of Accountancy Arusha (IAA) as a case study. The study population was all 187 teachers at IAA, through which a sample size of 97 participants was used for this study. The study employed a quantitative research approach and a descriptive research design to conduct the study. In data analysis, the study employed descriptive analysis to analyse data through mean, standard deviation, frequencies and percentages, where SPSS version 26 aided the data analysis process. The study found that the majority of respondents are unwilling to adopt online assessment at IAA due to technical, academic, and security concerns. Based on these findings, the study concluded that management support is critical in providing teachers with appropriate knowledge on the benefits and needs of using online assessment in Tanzanian public higher learning institutions, as well as providing teachers with appropriate technological and pedagogical know-how on how to best use different online assessment software to create appropriate online exams. Also, to use the most up-to-date versions of the online management system with all the appropriate plug-ins to support online assessment. Lastly, management should equip their institutions with appropriate online assessment software, hardware, and stable electricity.